Association between regular participation in sports and leisure time behaviors in Brazilian adolescents: A cross-sectional study - Fernandes, Romulo Araujo [UNESP]; Freitas Junior, Ismael Forte [UNESP]; Cardoso, Jefferson Rosa; Vaz Ronque, Enio Ricardo; Loch, Mathias Roberto; de Oliveira, Arli Ramos (Biomed Central Ltd., 2008)
Background: The belief that adolescents engaged in sports increase their overall physical activity level while simultaneously decreasing physical inactivity has been the foundation of many intervention programs in developing countries. The aim of this study was to analyze the association between regular participation in sports and both active behaviors and TV viewing during leisure time.Methods: A total of 1752 Brazilian adolescents (812 = male and 940 = female) participated in this study. Regular participation in sports, as well as active behaviors ( exemplified by walking or cycling) and TV viewing during leisure time were assessed by means of a questionnaire. The chi-square test analyzed the association between sports practice and leisure time behaviors, and the Poisson regression with robust variance indicated the magnitude of these associations.Results: The prevalence of regular participation in sports was 14.8% ( 95% confidence interval 13.2% to 16.5%). After adjustment for all confounders, participation in sports was associated with, at the highest frequency, cycling (PR = 2.55 [1.80-3.60]) and walking ( PR = 2.69 [1.98-3.64]) during leisure time. However, there was not an association between the participation in sports and frequency of TV viewing ( PR = 1.28 [0.81-2.02]).Conclusion: This study presented data indicating that the regular participation in sports is positively associated with a higher frequency of physically active behaviors during leisure time. However, the results did not support the hypothesis that the engagement in sports necessarily decreases leisure time spent in TV viewing.